Estimation of unknown functions of iterative difference inequalities and their applications - Luo, R.; Wang, W.; Xu, Honglei (Hindawi Publishing Corporation, 2014)
We establish some new nonlinear retarded finite difference inequalities. The results that we propose here can be used as tools in the theory of certain new classes of finite difference equations in various difference situations. We also give applications of the inequalities to show the usefulness of our results.